2020
DOI: 10.1088/1555-6611/ab8a51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er,Cr:YSGG laser irradiation and self-etch adhesive systems on hypermineralized dentin: a bond strength evaluation

Abstract: Over time teeth are exposed to several physical-chemical alterations, which may change the dental structure. Therefore, dental clinicians must be aware of how to manage the altered tissue. Laser irradiation and self-etch adhesives may be an option in this situation. This study aimed to evaluate the bond strength of self-etch adhesive systems associated with different treatments on hypermineralized dentin. 80 bovine incisors were distributed into two groups: Universal (3M ESPE; n = 40) and Optibond All in One (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(78 reference statements)
1
1
0
Order By: Relevance
“…In the literature, it has been concluded that erbium laserirradiated enamel shows morphological and chemical changes resulting from micro-explosions during laser ablation. 17,18 Zones of melting, crystallization, and microcracks have been reported in previous studies. However, these alternations of the irradiated enamel surface should be minimal if adequate water cooling is used.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the literature, it has been concluded that erbium laserirradiated enamel shows morphological and chemical changes resulting from micro-explosions during laser ablation. 17,18 Zones of melting, crystallization, and microcracks have been reported in previous studies. However, these alternations of the irradiated enamel surface should be minimal if adequate water cooling is used.…”
Section: Discussionsupporting
confidence: 65%
“…31 A higher gap formation (%) mean observed for the W group could be due to an increase in acid resistance of Er,Cr:YSGG laser irradiated dentin, as concluded in earlier studies. 17,18 This alternation in the acid resistance property is expected to negatively affect resin infiltration into the irradiated dentin. 33 The adhesive used in the current study has an ultra-mild acidity (pH of 2.7), which has a weak etching effect on the acidic functional monomer.…”
Section: Discussionmentioning
confidence: 99%